Recent Development of Corrosion Protection Strategy Based on Mussel Adhesive Protein - Zhang, Fan; Pan, Jinshan (Frontiers in Materials, 2019)
Many of traditional anti-corrosion approaches using chromate are effective but hazardous to natural environment and human health, so development of green and effective alternatives is desirable. One of the mussel adhesive proteins derived from mussel byssus presents extraordinary adhesion to steel surface and exhibits film-forming and corrosion inhibition properties. Novel strategies for enhancing the corrosion inhibition of steel by the protein have been demonstrated recently. The protein together with ceria nanoparticles presents a great potential for the development of new corrosion inhibitors and thin films that are ‘green’ and ‘effective’, and have ‘smart’ protection properties.